Navigating Disruption: A Survey of the Impact of Artificial Intelligence on the Indonesian Translation Industry: Menavigasi Disrupsi: Survei Dampak Kecerdasan Buatan terhadap Industri Penerjemahan Indonesia - Sunardi, FX Dono (Kementerian Sekretariat Negara Republik Indonesia, 2025)
The rapid emergence of artificial intelligence (AI) has introduced significant disruptive forces to the global language industry. While this technological shift is widely acknowledged, its specific impact on the Indonesian translation market, particularly from the perspective of industry practitioners, has remained an under-researched area. This study addresses this gap by employing a mixed-method approach, using an online survey to collect both quantitative and qualitative data from 10 (ten) Indonesian translation agencies and freelancers. The research reveals a paradoxical duality: while AI is widely perceived as a powerful tool for enhancing translation speed and efficiency, this has not translated into a corresponding increase in revenue. The data suggests that AI has compelled a shift in business models towards lower-rate post-editing services, while simultaneously creating new market segments. The findings indicate that the industry is not facing displacement but is undergoing a strategic transformation. Successful practitioners are those who embrace AI as an augmenting tool rather than a threat, specializing in high-value, creative, and culturally sensitive domains where human expertise remains paramount.